Probability analysis of setback distance based on structural damage near earthquake-fault-rupture. Issue 4 (September 2019) - Zhang, Jianyi; Bo, Jingshan; Li, Ping; Shen, Chao
Abstract: The probabilistic analysis method is the inevitable result of the development of engineering seismic science and adapts to the current level of people's understanding. This paper systematically summarizes the seismic damage of the engineering structures near the surface rupture zone of strong earthquakes in Yushu earthquake, Wenchuan earthquake and Jiji earthquake in recent years. According to the quantitative relationship between building damage index and distance, probability analysis results of the setback distance is given. This result is easy to popularize and apply, and lays a foundation for probabilistic risk analysis of buildings close to the surface rupture zone of strong earthquakes.